Dynamic Modeling and Flight Control Design for Multicopter - Bunjaku, Drilon; Nadzinski, Gorjan; Stankovski, Mile; Stefanovski, Jovan (International Review of Aerospace Engineering, 2018)
This paper presents a step by step dynamic modeling of the multicopter – quadcopter based on Newton Euler formalism, including the dynamics of the motor and the propellers. The linearization of the nonlinear mathematical model of the quadrotor is derived systematically when yaw angle is not 0 . Consequently, the simulation model of the flight controller based on the cascade control has been designed, which ensures a stabilization of the quad rotor and a robust-like trajectory tracking performance. The proposed cascade control strategy including the outer inverse dynamics provides controlling of the yaw orientation angle. The comparison of a use of a linear cascade PID-PD and the combination of PID-MPC is performed on 3D referent trajectories tracking with and without the presence of periodic external torque disturbances. The results are obtained from the MATLAB simulation model.
Keywords: Quadrotor dynamics, Control system design, Flight controller, Trajectory tracking